2009
DOI: 10.1111/j.1600-0722.2009.00672.x
|View full text |Cite
|
Sign up to set email alerts
|

Is diagnostic delay related to advanced‐stage oral cancer? A meta‐analysis

Abstract: Diagnostic delay in oropharyngeal cancer may be associated with poor prognosis. As controversy exists on this topic because of contradictory results, the aim of this study was to perform a systematic review of the relationship between total diagnostic delay and advanced disease stages. A systematic search of MEDLINE, EMBASE, and ISI proceedings was made to identify observational studies that provided relative risks (RRs) and 95% confidence intervals (CIs) for patients with confirmed pathological diagnosis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
160
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(171 citation statements)
references
References 42 publications
(77 reference statements)
2
160
0
9
Order By: Relevance
“…4 These findings are in contrast to a systematic review of 27 studies by Goy et al, 5 also published in 2009, which found no consistent positive association between diagnostic delay in any of the head and neck cancer sites analyzed (all head and neck sites combined, oral cavity, pharynx, and larynx) and advanced-stage disease. Goy et al 5 decided that a quantitative synthesis using meta-analysis could not be conducted because of the heterogeneity of the studies.…”
Section: Commentary and Analysismentioning
confidence: 61%
See 1 more Smart Citation
“…4 These findings are in contrast to a systematic review of 27 studies by Goy et al, 5 also published in 2009, which found no consistent positive association between diagnostic delay in any of the head and neck cancer sites analyzed (all head and neck sites combined, oral cavity, pharynx, and larynx) and advanced-stage disease. Goy et al 5 decided that a quantitative synthesis using meta-analysis could not be conducted because of the heterogeneity of the studies.…”
Section: Commentary and Analysismentioning
confidence: 61%
“…This study's objective was to perform a systematic review and meta-analysis to investigate whether total diagnostic delay was associated with advanced disease stages. 4 Total diagnostic delay refers to the period elapsed between the first symptom or sign and the definitive diagnosis. There are generally 2 to 3 stages of total diagnostic delay.…”
Section: Commentary and Analysismentioning
confidence: 99%
“…1,2 The point is clearly made that absence of bleeding on probing is a very significant indicator for periodontal stability. 2 Lack of gingival bleeding also suggests stability. Clinical attachment loss (CAL) is stated as a measure of periodontal disease history rather than current activity.…”
Section: False Negative Resultsmentioning
confidence: 99%
“…Despite this, half of OPSCC diagnoses are made at stages III or IV, which have survival rates of 20-50% depending on the subsite (Gomez et al, 2010;Gomez et al, 2009). As well as improving survival rates (by up to 90% for early stage cancers) (Bagan, Sarrion & Jimenez, 2010), evidence suggests that an early diagnosis can also decrease the morbidity associated with treatment (Gomez et al, 2010).…”
Section: Importance Of Early Diagnosismentioning
confidence: 99%
“…Tumour staging at the time of OPSCC diagnosis is recognised to be an imperative prognostic marker for survival (Gomez et al, 2009). Despite this, half of OPSCC diagnoses are made at stages III or IV, which have survival rates of 20-50% depending on the subsite (Gomez et al, 2010;Gomez et al, 2009).…”
Section: Importance Of Early Diagnosismentioning
confidence: 99%